Colloidal synthesis of 1-D van der Waals material Nb2Se9: study of synergism of coordinating agent in a co-solvent system - Kim, Tae Yeong; Woo, Chaeheon; Choi, Kyung Hwan; Dong, Xue; Jeon, Jiho; Ahn, Jungyoon; Zhang, Xiaojie; Kang, Jinsu; Oh, Hyung Suk; Yu, Hak Ki; Choi, Jae Young (Nanoscale, 2022)
Low-dimensional Nb2Se9 nanocrystals were synthesised through a simple one-pot colloidal synthesis with C18 organic solvents (octadecane, oleylalcohol, octadecanethiol, octadecene (ODE), and oleylamine (OLA)) of varied terminal functional groups. The solvent with high reducing power facilitated the nucleation of the nanoparticle, lowering threshold concentration and broadening the concentration spectrum. As a solvent, reducing agent, and capping agent, ODE functions as a primary factor in the synthesis of high-quality Nb2Se9 nanorods. We further discuss the unique adhesion role of ODE under the co-solvent system and demonstrate morphology control through synergism between ODE and OLA, verified by the electrochemical measurements.
Keywords: Colloidal synthesis; Coordinating agents; Cosolvents; Low dimensional; Octadecene; One pot; Simple++; Solvent system; Synthesised; Van der Waal